![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(x\left(x-2\right)+x-2=0\)
\(\Leftrightarrow\left(x-2\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\x+1=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
Vậy ...
b/ \(5x\left(x-3\right)-x+3=0\)
\(\Leftrightarrow\left(5x-1\right)\left(x-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}5x-1=0\\x-3=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{5}\\x=3\end{matrix}\right.\)
Vậy ..
a. x.(x - 2) + x - 2 = 0
\(\Leftrightarrow\)x(x-2)+(x-2)=0
\(^{_{ }\Leftrightarrow}\)(x-2)(x+1)=0
\(\left[{}\begin{matrix}x-2=0\\x+1=0\end{matrix}\right.\Leftrightarrow\)\(\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
Vậy x\(\in\)\(\left\{2;-1\right\}\)
b. 5x(x-3)-(x+3)
\(^{_{ }\Leftrightarrow}\)5x(x-3) + (x-3) = 0
\(^{_{ }\Leftrightarrow}\)(x-3)(5x+1) = 0
\(\Rightarrow\)\(\left\{{}\begin{matrix}x-3=0\\5x+1=0\end{matrix}\right.\)\(\Rightarrow\)\(\left\{{}\begin{matrix}x=3\\x=\dfrac{-1}{5}\end{matrix}\right.\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{1}{1-x}\)+\(\dfrac{1}{1+x}\)+\(\dfrac{2}{1+x^2}\)+\(\dfrac{4}{1+x^4}\)+\(\dfrac{8}{1+x^8}\)+\(\dfrac{16}{1+x^{16}}\)
=
=\(\dfrac{4}{1-x^4}\)+\(\dfrac{4}{1+x^4}\)+\(\dfrac{8}{1+x^8}\)+\(\dfrac{16}{1+x^{16}}\)
=\(\dfrac{8}{1-x^8}\)+\(\dfrac{8}{1+x^8}\)+\(\dfrac{16}{1+x^{16}}\)
=\(\dfrac{16}{1-x^{16}}\)+\(\dfrac{16}{1+x^{16}}\)
=\(\dfrac{32}{1-x^{32}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Rút gọn :
4x(x-2) - (5x-2)(2+5x)
= 4x(x-2) + ( 2-5x)( 2+5x)
= \(4x^2-8+4-10x^2\)
= \(-6x^2-4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
a. Đặt x-7 = t
\(\Rightarrow x-3=t+4;x-11=t-4\)
\(\Rightarrow\left(x-3\right)^2+\left(x-11\right)^2=\left(t+4\right)^2+\left(t-4\right)^2=t^2+16+8t+t^2+16-8t=2t^2+32\)
Vì \(2t^2\ge0\) nên: \(2t^2+32\ge32\)
Dấu "=" xảy ra \(\Leftrightarrow2t^2=0\)
\(\Leftrightarrow t^2=0\)
\(\Leftrightarrow\left(x-7\right)^2=0\)
\(\Leftrightarrow x-7=0\Leftrightarrow x=7\)
Vậy \(Min_A=32\Leftrightarrow x=7\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,(3+x)(x2-9)-(x-3)(x2+3x+9)
=(3x2-27+x3-9x)-(x3-27)
=3x2-27+x3-9x-x3+27
=3x2-9x
=3x(x-3)
b,(x+6)2-2x(x+6)+(x-6)(x+6)
=x2+12x+36-2x2-12x+x2-36
=0
a) \(\left(3+x\right)\left(x^2-9\right)-\left(x-3\right)\left(x^2+3x+9\right)\)
\(=\left(3x^2+x^3-27-9x\right)-\left(x^3-27\right)\)
\(=3x^2+x^3-27-9x-x^3+27\)
\(=3x^2-9x\)
b) \(\left(x+6\right)^2-2x\left(x+6\right)+\left(x-6\right)\left(x+6\right)\)
\(=\left(x^2+12x+36\right)-\left(2x^2+12x\right)+\left(x^2-36\right)\)
\(=x^2+12x+36-2x^2-12x+x^2-36\)
\(=0\)
\(i^3\)
\(i\cdot i\cdot i=i^2\cdot i=1\cdot i=i\)